PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KEPEMILIKAN KELUARGA TERHADAP INTERNET FINANCIAL REPORTING - Monica Dameuli; Idrianita Anis (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
The purpose of this study is to examine the effect of corporate governance mechanism and family ownership on internet financial reporting (IFR) of manufacturing firms listed in Indonesia Stock Exchange in the year 2012. Corporate governance mechanism in this study is measured by the effectiveness of board of commissioners and the effectiveness of audit committee. The result shows that theeffectiveness of board of commissioner, the effectiveness of audit committee, and family ownership do not significantly affect IFR.Further examination is done by dividing the effectiveness of board ofcommissioners and the effectiveness of audit committee into several categories of mechanism, which are independence, activities, size and skill & competence. However, there are still no evidence that board of commissioners’ independency, board of commissioners activities, size of board of commissioners, board of commissioners’ skill and competency, audit committee activity, size of audit committee, and audit committee’s skill and competency as well as family ownership affect IFR. This study also uses control variables such as profitability, liquidity, leverage,and company size. The result shows that profitability and company size significantly positive affect IFR.